Three heads are better than one: Psychiatry trainees' experiences of a psychotherapy written case supervision group with three co-supervisors. (April 2022) - Matta, Gabrielle; Ryan, Tom; Hartman, David
Objective: The aim of this project was to evaluate the experiences of Royal Australian and New Zealand College of Psychiatrists (RANZCP) trainees in a regional centre who participated in a psychodynamic psychotherapy written case supervision group with three co-supervisors. Method: A web-based survey was sent to RANZCP trainees. Descriptive statistics were performed, and written feedback was analysed. Results: A total of 8 of 10 eligible trainees completed the survey. All respondents stated that the group met their training needs. The average rating of feeling understood by supervisors was 91 (maximum 100). Positive feedback was received about the variety and breadth of experience provided by the co-supervisors. Trainees felt that 1:1 supervision was important to complement group supervision. Conclusions: The supervision group model with three co-supervisors is competently meeting the training needs of RANZCP trainees as well as providing a deep learning experience. This model may be of use in other services, particularly in regional settings.